PENGARUH PENGGUNAAN METODE PEMBELAJARAN KERJA KELOMPOK DAN MOTIVASI TERHADAP HASIL BELAJAR BATIK SISWA KELAS XI DI SMKN 8 PADANG - PUTRI SARI RAMADHANI, Dr. Ramalis Hakim, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2018)
This research aims to see the influence of group learning method and motivation learning method toward sudents` batik learning outcome in SMKN 8 Padang. The population of the study are eleven graders DPK texile. Saturation sampling is used as the sampling technique in this study. This research uses 2x2 factorial. The instrument used are test of learning outcome and motivation questionnaire by using Likert scale. Instruments have been tested to know the index vadility, reliability, with the degree of reliability α = 0,05. Research result proves that: (1) the influence of XI students` learning batik outcome in SMK N 8 Padang taught by using group learning method is significant. (2) the influence of XI students` learning batik outcome who have high motivation in SMK N 8 Padang taught by using group learning method is not significant. (3) the influence of XI students` learning batik outcome who have low motivation in SMK N 8 Padang taught by using group learning method is significant. Based on these findings, it can be concluded that group learning method is one of the learning methods that provides a positive effect on improving learning outcomes, especially for students who have low learning motivation.Keywoards: Learning Method, Group Work, Learning Motivation